Variabilities in determining air exchange rates in naturally ventilated dairy buildings using the CO2 production model. (October 2018) - König, Marcel; Hempel, Sabrina; Janke, David; Amon, Barbara; Amon, Thomas
Abstract : Gaseous emissions from livestock buildings have been a research focus for many years. In particular, quantifying emissions from naturally ventilated buildings is not trivial because it requires accurately determining the air exchange rate (AER) and representative gaseous concentration values in the exhaust and in the incoming air. Improvements are required for the method for estimating AERs and for selecting representative sampling points and locations in naturally ventilated dairy buildings (NVB). The objective of this study was to investigate the magnitude and sources of uncertainties in calculating AERs. A long-term experiment was performed in an NVB located in north-east Germany. CO 2 concentrations were continuously measured inside the barn at eight uniformly distributed points and outside the barn at four points. Sensitivity studies on the calculation of AER were performed by varying the indoor and outdoor sampling points, sampling duration and animal parameters used for the calculation. The sensitivity results were compared to the best available data approximation (BADA), which is based on the best knowledge of these parameters. All factors were evaluated and ordered in terms of their influence on AER calculation and uncertainty. The results show that the sampling duration and the number and location of indoor sampling points have the largest effects on AER uncertainty. Data on milk yield and days since insemination have the lowest influence on AER uncertainty. The information collected in this long-term study is very important for planning measurement campaigns in the future. Highlights: Sufficient measurement duration is crucial for quality of AER estimation. Optimal sampling point location inside the barn has large influence on AER. Individual sampling points in the centre of the barn show better results. Animal parameter has moderate effect on the accuracy for AER.